Evaluation of oral health status and quality of life of head and neck cancer patients after radiation therapy - Silva Miguel Franklin Alves; Melo Ana Valesca Gurjão; Barbosa Kevan Guilherme Nóbrega; Pereira Jozinete Vieira; Alves Polliana Muniz; Gomes Daliana Queiroga de Castro (Serbian Medical Society - Dental Section, Belgrade, 2014)
Introduction. Neoplasm of the head and neck can be treated surgically, by radiation, chemotherapy, or using combination of these methods. In contrast to surgical and radiation treatment which mostly have a local effect, chemotherapy in addition to local have also a systemic effect. Both XRT in oral region and chemotherapy can affect oral health. The aim of this study was to assess the oral health status and quality of life in patients with head and neck cancer after receiving radiation therapy. Material and Methods. Quantitative, analytical and cross-sectional research methods along with the application of UW-QOL questionnaire version 4, were used. Seventy one patients of the outpatient facilities at two cancer hospitals in the state of Paraнba, Brazil, were included in the study. Oral health status was evaluated using the Lockhart and Clark criteria. Linear Poisson and Logistic Regression tests were applied to assess associations between the variables using a significance level of 5%. Results. Of the total number of patients, 71.83% were male, the average age was 62 years and 57.74% were non-Caucasian. The group that received dental monitoring and follow-up attained the highest (830.13) Quality of life scores, including: "pain" (93.13) and "taste" (83.07). The highest score for oral health in the group that did not receive dental monitoring and follow-up treatment was 4.08 for "oral hygiene". Conclusion. Dental monitoring and follow-up should begin before radiation therapy, given that both the illness and methods used for the treatment negatively affect patients' quality of life.